The Death of American Studies - Simon J. Bronner (European Journal of American Studies)
Using the life-course metaphor in Richard M. Dorson’s landmark address “The Birth of American Studies” in Warsaw on the occasion of forty years since the start of the groundbreaking Harvard program in American Studies, this essay questions whether American Studies in the forty years afterwards suffered a fatal malaise. It applies the analytical approach of historiographer Gene Wise to identify “representative acts” that mark paradigm dramas resulting from tension in holding together an interdisciplinary field subject to schism and displacement. The essay posits that the American Studies movement as it was conceptualized within the American Studies Association in the United States went into decline in the late twentieth century, largely because of the association’s inability, or unwillingness, to resolve differences between “Americanist” research-based scholars, many international, working within an American Studies tradition identified by Dorson and those coming to it from outside American Studies supposedly following “critical” thought. The critical school came to be dominant in the American Studies Association with a paradoxical attitude undermining the very subject, and organization, that it purports to promote. Looking at the work of American Studies programs and organizations beyond the American Studies Association, the essay suggests that it is possible to revitalize American Studies on the model of “Americanistics” sustained primarily in European centers and associations.